Interpersonal Communication with the Deaf in the Metaverse Age - Idegham Dani; Anang Anas Azhar (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2022)
Tanjung Selamat Village is one of the villages located in Sunggal District, Deli Serdang Regency, Nort Sumatra Province, Indonesia. According to data from the Tanjung Selamat Village population census, this village is a village with a low level of disability. There are only 0.001% of the total population with disabilities. However, technological advancements in the village have advanced, the community is familiar with the term metaverse, thia Cn be seen from the number of internet users in the village because the internet is part of the metaverse. The goal of this study was to determine the evolution of metaverse use for deaf people. This study combines descriptive research with an observational approach to provide a comprehensive picture of deaf people's use of the metaverse. This study included four participants: the village head of Tanjung Selamat Village, two people deaf and their families who are natives the village of Tanjung Selamat, and one metaverse user who are in the city of Medan. According to the findings of this study, the deaf in Tanjung Selamat Village have not been able to use metaverse to facilitate communication, but the seeds of technological progress have been used by the deaf, as evidenced by their use of an application to send messages as an easy way to communicate. On the other hand, there is great hope that technological advancements, particularly the metaverse, will reach all corners of the globe and be put to good use.